Analisis Efisiensi Biaya Produksi Batako, Batu Bata Merah dan Hebel Dengan Penerapan Metode Target Costing - maulidi, syahrul; Ariansyah , Dedek; Pramanda, Heru; Bunyamin, Bunyamin; Hady, Munirul (Universitas Iskandar Muda, 2025)
This research is driven by the importance of cost efficiency in the local building material industry in Aceh, especially in addressing fluctuations in raw material prices, high labor costs, and limited production technology. The study aims to analyze the cost efficiency of producing three types of construction materials batako (concrete blocks), red bricks, and lightweight bricks (hebel) using the target costing method. The research was conducted at three local business units in Aceh: Usaha Aneka Lobang Angin (batako), Sentral Batu Bata (red bricks), and BUMG Pulo Kemiro (hebel). A descriptive quantitative approach was used, with data collected through observation, interviews, documentation, and literature review. The analysis showed that the cost efficiency levels of each product were 93.33% for batako, 92.96% for hebel, and 90.00% for red bricks. These figures were calculated by comparing the target cost with actual production costs, based on a 25% profit margin. Factors affecting efficiency include raw material prices, production methods, daily productivity, and overhead costs. Among the three, batu bata merah was identified as the most efficient and suitable product for development by small and medium enterprises (SMEs) in Aceh. The application of the target costing method helps business actors control costs, improve production efficiency, and support sustainable business growth.